Trade liberalisation in the East African Community: the need for competition law and policy in Uganda - Mugaino, Baker (Department of Commercial Law, 2016)
This study will show the relevance of competition policy and law is not only stopping anti-competitive practices but also its role in complimenting government reforms and policies in Uganda. The research will contribute to the development of the relevant competition law legislation for Uganda. The motivation of the study is derived from the competition challenges facing Uganda today, a country that has liberalised and privatised its economy but has no competition policy and law.